2018
DOI: 10.1016/j.hemonc.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Thrombo-hemorrhagic liability in children with congenital heart diseases

Abstract: Patients with CHD-both cyanotic and acyanotic-have variable degrees of increased liability for both thrombosis and hemorrhage that represents some sort of adaptation to preserve hemostasis and to protect these patients against the clinical presentation of both thrombosis and bleeding. This is to say that CHD patients have their own point of balance between thrombogenicity and bleeding liability. Wide-scale studies are needed to detect the normal levels of different thrombohemorrhagic parameters of these patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Additionally, CHD may be independently associated with abnormal hemostasis. In a study by Shebl, et al, 14) abnormal platelet counts, coagulation times, and selectin and platelet factor 4 levels were common in patients with CHD and constituted high-risk factors for both bleeding and thromboembolism. Similarly, Giang, et al 15) reported an approximately 8-fold increase in the relative risk of hemorrhagic stroke in children and young adults with CHD, compared to matched controls from the general population.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, CHD may be independently associated with abnormal hemostasis. In a study by Shebl, et al, 14) abnormal platelet counts, coagulation times, and selectin and platelet factor 4 levels were common in patients with CHD and constituted high-risk factors for both bleeding and thromboembolism. Similarly, Giang, et al 15) reported an approximately 8-fold increase in the relative risk of hemorrhagic stroke in children and young adults with CHD, compared to matched controls from the general population.…”
Section: Discussionmentioning
confidence: 98%
“…Many subsequent studies demonstrated the prolongation of clotting times in children with CHD. However, these studies demonstrated a more global impairment of the hemostatic profile, including decreased levels of FII, FV, FVIII, FIX, FX, and natural inhibitors of coagulation [4,[10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The prolongation of PT in association with reduced FVII levels observed in our study indicates that a derangement towards hemorrhage is evident early in the course of the disease, even preoperatively. Shebl et al reported an increased liability both to hemorrhage and thrombosis in children with CHD, as demonstrated by thrombocytopenia, prolongation of clotting times, and increased levels of soluble markers of platelet and endothelial activation [17].…”
Section: Discussionmentioning
confidence: 99%
“…These patients are prone to both hypercoagulability and bleeding. Simple alteration of coagulation profiles may not accurately predict either event due to the complex dynamics influencing thrombosis and bleeding ( 6 ).…”
Section: Discussionmentioning
confidence: 99%